Asymmetric organocatalytic reductions mediated by dihydropyridines - CONNON, STEPHEN (Royal Society of Chemistry, 2007)
Catalytic asymmetric reduction reactions have long been the preserve of the transition metal catalyst. Inspired by the myriad efficient enzyme-catalysed reduction reactions routine in biological systems, chemists have recently begun to design chiral metal-free organocatalysts that employ synthetic dihydropyridine NADH analogues as the hydride source with impressive results. Recent developments in this burgeoning field are discussed.
PUBLISHED
Keywords: Biochemistry; dihydropyridines